The Effect of Heparin and Its Preparations on Disseminated Intravascular Coagulation Mortality and Hospitalization: A Systematic Review - Omidkhoda, Navid; Abedi, Farshad; Ghavami, Vahid; Rahimi, Hossein; Samadi, Sara; Arasteh, Omid; Mohammadpour, Amir Hooshang (International journal of clinical practice (Esher), 2022)
Background and Aim. Disseminated intravascular coagulation (DIC) is a critical clinical condition that is expressed by systemic activation of the homeostatic system, leading to elevation of thrombin deposition and result in microvascular thrombi. Heparin makes a good effect on hypercoagulability states through inhibition of thrombin. The present study aimed to summarize and discuss the results of randomized clinical trials and cohort studies regarding the effect of heparin and its preparations on DIC mortality and duration of hospitalization. Methods. The databases of PubMed, Scopus, Embase, and Web of Science were searched systematically up to November 2021. The quality of RCTs was assessed by Cochrane Collaboration’s tool and the risk of bias was assessed for cohort studies through NOS score. Results. Out of 3288 articles, eight studies were eligible to be included in this study. Our review retrieved six RCTs and two retrospective cohort studies consisting of 950 participants diagnosed by DIC. A significant effect of heparin on DIC mortality was identified in four studies. Furthermore, heparin was used as a control group in three studies. Conclusions. We concluded that administration of heparin and its preparations in DIC patients could reduce the mortality rate and duration of hospitalization, especially in the earlier stages of DIC.